Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s40141-014-0074-x
|View full text |Cite
|
Sign up to set email alerts
|

Sports Medicine Considerations for the Paralympic Athlete

Abstract: Increased participation and expanded public interest in the Paralympic Games underline the growing importance of competitive sports opportunities for individuals with disabilities. Injury surveillance is increasingly recognized as a key element of sports medicine research, and recent work has suggested that rates of injury, anatomic location of injury, and associated illness may in fact differ in athletes with disabilities. A greater understanding of the patterns of injury and illness for athletes with disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…The second important finding was the high incidence of injury in the shoulder/arm/elbow complex (39 injuries; IR of 5.7 [95% CI 4.2 to 7.8]), with 27 of these injuries reported for the shoulder joint. The shoulder joint has been highlighted in both the summer and winter setting for athletes with impairment, mainly for wheelchair users who use their upper body to perform both their sport and activities of daily living 1 4 5 19–22. In the current study, sports in which athletes used their arms for power and stability during high-speed propulsion, namely para ice hockey (n=21; 56% of all injuries), para Nordic skiing (n=13; 50% of all injuries) and para alpine skiing (n=13; 30% of all injuries) had a higher number of reported injuries in this area.…”
Section: Discussionmentioning
confidence: 75%
“…The second important finding was the high incidence of injury in the shoulder/arm/elbow complex (39 injuries; IR of 5.7 [95% CI 4.2 to 7.8]), with 27 of these injuries reported for the shoulder joint. The shoulder joint has been highlighted in both the summer and winter setting for athletes with impairment, mainly for wheelchair users who use their upper body to perform both their sport and activities of daily living 1 4 5 19–22. In the current study, sports in which athletes used their arms for power and stability during high-speed propulsion, namely para ice hockey (n=21; 56% of all injuries), para Nordic skiing (n=13; 50% of all injuries) and para alpine skiing (n=13; 30% of all injuries) had a higher number of reported injuries in this area.…”
Section: Discussionmentioning
confidence: 75%
“…It also shows that such a positive trend in track-and-field athletics contrasts with the stagnation in the performance of most Olympic track-and-field events. As advances occur in athletic performance-related aspects, like talent identification, prevention of injuries, training methodology, and sport policies (Houlihan & Chapman, 2017;Patatas et al, 2018;Slocum, Blauwet, & Anne Allen, 2015), future performance gains in Paralympic athletes are a strong possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this, it is worth mentioning that those investigations performed during the Paralympic Games used an accurate methodology but provided limited information on Para judo. Finally, it should be considered that a greater understanding of the patterns of injury for athletes with disabilities has important clinical implications for rehabilitation and sports medicine physicians 70 . However, very few studies reported information on injuries’ severity, on factors that can increase injury risk (i.e., age, sex, years of experience, category, competition level) and especially on the influence of VI.…”
Section: Discussionmentioning
confidence: 99%